Superomedial pedicle skin-reducing mastectomy in ptotic and large-sized breasts with two-stage reconstruction through transaxillary video-assisted technique: An effective surgical and anesthetic approach - Di Monta, G.; Marone, U.; Avino, F.; Esposito, E.; Cepparulo, V.; Morra, E.; Saponara, R.; Bifulco, F.; Cuomo, A.; Cascella, M.; Mori, S. (Frontiers in Surgery, 2023)
Introduction Skin reducing mastectomy procedure has been applied to several surgical techniques in which the subcutaneous mastectomy is associated with various types of skin reduction, with preservation of a lower dermal flap to reinforce the inferior lateral seat of an implant. Aim of the study is to present a case series of patients with pendolous/ptotic and/or large sized breasts treated for breast cancer at Breast Surgery Unit at Istituto Nazionale Tumori IRCCS Fondazione “G. Pascale”, Naples – Italy, with the technique of supero-medially pedicle skin reducing mastectomy, with two stages reconstruction, with transaxillary video-assisted technique, when a postoperative radiotherapy was indicated. We verified its effectiveness by discussing its results, especially in patients who are candidates for post-mastectomy radiotherapy Materials and methods A single-center retrospective study was performed between January 2020 to March 2021 on a prospectively filled database of conservatives mastectomies. Of these total 64 patients who underwent nipple/skin sparing mastectomies tecqnique in the mentioned period, 17 (mean age 46 years, range 30-62) were treated with superomedial pedicle skin reducing mastectomy, with two stages breast reconstruction through transaxillary video-assisted replacement expander with definitive prosthesis and controlateral symmetrization, in those patients selected to post mastectomy radiotherapy. Results We had only three minor complications. No flap necrosis, no infections, no breast seromas and no reconstructive failures were observed. During follow-up of the patients treated with videoassisted reconstruction, there were no cases of infection, hematoma, implant rupture, or suture dehiscence in the reconstructed breast. Discussion The skin reducing mastectomy with supero-medial pedicle, is safe and reliable procedure to treat breast cancer in selected patients i.e. those with with pendolous/ptotic and or large sized breasts. Especially in patients who undergo post mastectomy radiotherapy, the two-stages reconstruction with video-assisted transaxillary endoscopic approach can find its main indication, using incisions positioned far from the mammary region, offering numerous advantages.